Association Between Air Pollution and Viral Infection in Severe Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Choi, Juwhan; Shim, Jae Jeong; Lee, Myung Goo; Rhee, Chin Kook; Joo, Hyonsoo; Lee, Jin Hwa; Park, Hye Yun; Kim, Woo Jin; Um, Soo-Jung; Kim, Deog Kyeom; Min, Kyung Hoon (Journal of Korean medical science, 2023)
Respiratory pathogen infections and air pollution are main causes of acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Air pollution has a direct effect on the airway epithelial barrier and the immune system, which can have an influence on infection. However, studies on the relationship between respiratory infections and air pollutants in severe AECOPD are limited. Thus, the objective of this study was to investigate the correlation between air pollution and respiratory pathogen in severe AECOPD. This multicenter observational study was conducted by reviewing electronic medical records of patients with AECOPD at 28 hospitals in South Korea. Patients were divided into four groups according to the comprehensive air-quality index (CAI) used in Korea. Identification rates of bacteria and viruses of each group were analyzed. Viral pathogens were identified in 270 (36.7%) of 735 patients. Viral identification rate was different ( = 0.012) according to air pollution. Specifically, the virus detection rate was 55.9% in the group of CAI 'D' with the highest air pollution. It was 24.4% in the group of CAI 'A' with the lowest air pollution. This pattern was clearly seen for influenza virus A ( = 0.042). When further analysis was performed with particulate matter (PM), the higher/lower the PM level, the higher/lower the virus detection rate. However, no significant difference was found in the analysis related to bacteria. Air pollution may make COPD patients more susceptible to respiratory viral infections, especially influenza virus A. Thus, on days with poor air quality, COPD patients need to be more careful about respiratory infections.